2018
DOI: 10.1017/s1355617718000851
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury Burden Moderates the Relationship Between Cognitive Functioning and Suicidality in Iraq/Afghanistan-Era Veterans

Abstract: Objective: Suicidal ideation (SI) is highly prevalent in Iraq/Afghanistan-era Veterans with a history of mild traumatic brain injury (mTBI), and multiple mTBIs impart even greater risk for poorer neuropsychological functioning and suicidality. However, little is known about the cognitive mechanisms that may confer increased risk of suicidality in this population. Thus, we examined relationships between neuropsychological functioning and suicidality and specifically whether lifetime mTBI burden would moderate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
(158 reference statements)
0
11
2
Order By: Relevance
“…The present study also did not identify a significant association between social support and SI as found in previous literature (Pietrzak et al, 2010). Moreover, our exploratory analyses did not identify associations between cognitive functioning and SI, differing from a previous study in OEF/OIF/OND Veterans that found an association between worse memory functioning and SI (Crocker et al, 2019). However, this earlier study was specific to Veterans with TBI, was not specific to Veterans at risk for homelessness, utilized different neuropsychological measures, and included a larger sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study also did not identify a significant association between social support and SI as found in previous literature (Pietrzak et al, 2010). Moreover, our exploratory analyses did not identify associations between cognitive functioning and SI, differing from a previous study in OEF/OIF/OND Veterans that found an association between worse memory functioning and SI (Crocker et al, 2019). However, this earlier study was specific to Veterans with TBI, was not specific to Veterans at risk for homelessness, utilized different neuropsychological measures, and included a larger sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Many of the risk factors for suicidality and homelessness among Veterans overlap, including traumatic brain injury (TBI) history, psychiatric conditions, substance use disorder, low income, low social support, and cognitive dysfunction (Brenner et al, 2017; Crocker et al, 2019; Kang & Bullman, 2008; Lemaire & Graham, 2011; Metraux et al, 2013; Office of Suicide Prevention, 2019; Pietrzak et al, 2010; Tanielian & Jaycox, 2008; Tsai & Rosenheck, 2015; Twamley et al, 2019). Research suggests that Veterans with a history of homelessness are particularly vulnerable to suicidal behaviors (e.g., Culhane et al, 2019; Metraux et al, 2013; Tsai & Cao, 2019; Tsai et al, 2018).…”
mentioning
confidence: 99%
“…Notably, a similar threshold has been observed in other behaviorally and psychiatrically focused civilian and military studies. 44,45 Preliminary work from our lab also suggests that compensatory neurovascular processes occur even in those with fewer than two injuries, but are not evident in those three or more injuries. 80 Relatedly, although Table 1 focuses on mechanisms of injury related to their “most significant TBI,” many individuals reported experiencing injuries of other or mixed mechanisms as well.…”
Section: Discussionmentioning
confidence: 91%
“…These groupings were also based on similar studies exploring the negative influence of repetitive head-trauma on behavior in other Veteran samples. 44,45…”
Section: Methodsmentioning
confidence: 99%
“…Depression as a neurophychiatric pathology has an effect on quality of life deterioration (QOL) and on the neurocognitive functioning of people with this pathology. The data obtained by different [11][12][13][14][15] researches have found that depressive symptomatology affects the storage, consolidation and evocation of information, specifically on the inmediate verbal memory and in every aspect of it, likewise; it was found that depression is related to executive deficits [16][17][18], associated to the subcortical and the prefrontal cortex, frontal interactions, preventing the patients from regulating their decission making in different contexts, data which is also related to a clinical profile of severe cortical subcortical atrophy [19][20][21].…”
Section: Introductionmentioning
confidence: 99%